Museum XYZ, Major City, USA - Donnelly, Anne Cohn (SAGE Knowledge. Cases., 2017)
Museum XYZ built a beautiful facility in a large, Midwestern city. However, after opening to much acclaim, attendance began to fall off, finances were in a shambles, and there appeared to be a leadership void. The board hired two consultants to conduct a review to pinpoint the issues. This case discusses what the consultants learned, and the teaching note discusses what the board decided to do with the information.